PERBEDAAN KUALITAS PELAYANAN PADA PASIEN BPJS DAN PASIEN UMUM RAWAT INAP DI RUMAH SAKIT MUHAMMADIYAH MEDAN TAHUN 2019 - ODI SUPANDRI; OTNIEL KETAREN; LIA ROSA VERONIKA (JURNAL ILMIAH SIMANTEK, 2019)
Improving the quality of service is one of the most crucial issues in management, include in the government and the private sector. This happens because on the one hand the demans of the community towards improving the quality of services are getting bigger, while on the other hand the practice of service delivery has not experienced significant improvements so that it can have an impact on patient satisfaction. The purpose of this study was to determine the differences in the quality of care for general patients and BPJS’ patients in Muhammadiyah Medan Hospital 2019. The type of this research is correlation descrption with the cross sectional approach, Population used in this study was all inpatient patient Muhammadiyah Hospital in Januari 2019 as 260 people. Sample was a half of the population in this study. Sampling used the slovin formula. In accordance with the results of sample calculations obtained with a sample of 158 respondent with 110 people of BPJS’ patient and 48 people of general patient. Sampling procedure used accidental sampling, was the sampling was carried out in inpatient who happened to meet with researchers at Muhammadiah Medan Hospital. The result showed there is a difference in the service quality of general patients and BPJS’ patients in Muhammadiyah Medan Hospital with p value = 0.01 < 0,05. In connection with this, it is to improve patient satisfaction with services at Muhammadiyah Medan Hospital. It is better for the hospital to improve the quality ot they services especially in tangibles of hospital whose conditions are inadequate.